Oral health outcomes in an HIV cohort with comorbidities- implementation roadmap for a longitudinal prospective observational study - Temitope T. Omolehinwa; Sunday O. Akintoye; Marta Gabinskiy; Vincent Lo Re; Mel Mupparapu; Rosa Urbina; Douglas E. Schaubel; Patricia M. Corby (BMC, 2023)
Abstract Background Long-term antiretroviral therapy (ART) perpetually suppresses HIV load and has dramatically altered the prognosis of HIV infection, such that HIV is now regarded as a chronic disease. Side effects of ART in Patients With HIV (PWH), has introduced new challenges including "metabolic" (systemic) and oral complications. Furthermore, inflammation persists despite great viral load suppression and normal levels of CD4+ cell count. The impact of ART on the spectrum of oral diseases among PWH is often overlooked relative to other systemic complications. There is paucity of data on oral complications associated with ART use in PWH. This is in part due to limited prospective longitudinal studies designed to better understand the range of oral abnormalities observed in PWH on ART. Methods We describe here the study design, including processes associated with subject recruitment and retention, study visit planning, oral health assessments, bio-specimen collection and preprocessing procedures, and data management and statistical plan. Discussion We present a procedural roadmap that could be modelled to assess the extent and progression of oral diseases associated with ART in PWH. We also highlight the rigors and challenges associated with our ongoing participant recruitment and retention. A rigorous prospective longitudinal study requires proper planning and execution. A great benefit is that large data sets are collected and biospecimen repository can be used to answer more questions in future studies including genetic, microbiome and metabolome-based studies. Trial registration National Institute of Health Clinical Trials Registration (NCT) #: NCT04645693.